PENGARUH CSR (CORPORATE SOCIAL RESPONSIBILITY) TERHADAP CITRA PERUSAHAAN YUDITEX DI POLOKARTO - Ristina Dwi Astuti; Heni Susilowati (LPPM Politeknik Pratama, 2022)
The purpose of this study is to determine the effect of CSR (Corporate Social Responsibility) on Yuditex's corporate image in Polokarto. The sample is 85 respondents who were selected by accidental sampling technique from the population of the community around the Yuditex company in Polokarto. The data collected was quantified with a Liker scale of 1-5 then analyzed using multiple linear regression with the help of SPSS version 25. The findings of the study indicate that partially and simultaneously CSR (Corporate Social Responsibility) which includes Community Support, Diversity, and Environment has an influence on image Yuditex company in Polokarto.